Interação do algodoeiro BT submetido ao estresse hídrico e Alabama argillacea (Hübner) (Lepidoptera: Noctuidae) - Lima, Mauricio Silva de (2010)
The genetically modified cotton to produce toxins from the bacterium Bacillus thuringiensis (Bt) has the objective of offering plant resistance against lepidopteran larvae. The cotton crop cultivated in the Semiarid region can be subjected to the condition of water stress. Thus, this work investigated the expression of the Cry1Ac toxin in two varieties of Bt-cotton Acala 90B and NuOpal cultivated under the conditions of irrigated and water stress. In addition, the oviposition and feeding preference of adults and larvae of the cotton leafworm, Alabama Argillacea (Hübner), caged on these plants were studied. Cotton plants were cultivated under controlled conditions of irrigation to obtain water stress treatment in microparcels inside an open-sided greenhouse. Higher levels of Cry1Ac expression was found on top leaves of Bt-cotton for both varieties under water stress condition, and similar levels between plants with and without water stress in the other plant parts such as bracts, flower petals, and boll. Adults of A. argillacea did not exhibited preference for oviposition between Bt and non-Bt cotton plants. Likewise, 3- and 10-d-old A. argillacea larvae did not show food preference under a choice test comparing leaves of non-Bt and Bt-cotton plants. Otherwise, adults of A. argillacea showed lower oviposition on plants under water stress, and their larvae did not complete development fed non-Bt varieties cultivated under water stress condition. These results indicated that adults and larvae of A. argillacae do not recognize Bt-cotton plants to lay eggs and to feed, respectively. Further, cotton plants under water stress showed greater Cry1Ac toxin concentration on top leaves, interfered with the oviposition of A. argillacea irrespective of plant genotypes Bt and non-Bt, and with the larval development on non-Bt plants.